2008
DOI: 10.1007/s11251-008-9056-7
|View full text |Cite
|
Sign up to set email alerts
|

The effects of representational format on learning combinatorics from an interactive computer simulation

Abstract: The current study investigated the effects of different external representational formats on learning combinatorics and probability theory in an inquiry based learning environment. Five conditions were compared in a pre-test post-test design: three conditions each using a single external representational format (Diagram, Arithmetic, or Text), and two conditions using multiple representations (Text + Arithmetic or Diagram + Arithmetic). The major finding of the study is that a format that combines text and arit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 58 publications
1
31
0
4
Order By: Relevance
“…Other stijdies of combinatorics and probability learning have consistendy found that instmction based on formal representations alone is as effective as or more effective than grounded instmction (Belenky & Nokes, 2009;Kolloffel et al, 2009). This negative fmding was replicated in Experiment 2.…”
Section: Discussionmentioning
confidence: 67%
“…Other stijdies of combinatorics and probability learning have consistendy found that instmction based on formal representations alone is as effective as or more effective than grounded instmction (Belenky & Nokes, 2009;Kolloffel et al, 2009). This negative fmding was replicated in Experiment 2.…”
Section: Discussionmentioning
confidence: 67%
“…The tests contained 12 and 26 items respectively. The sensitivity and reliability of the test items have been established in recent years in a number of studies performed across Germany and The Netherlands (see e.g., Berthold and Renkl 2009;Eysink et al 2009;Gerjets et al 2009;Kolloffel et al 2009;Wouters et al 2007). The pre-test was aimed at measuring (possible differences in) the prior knowledge of the students.…”
Section: Representational Toolsmentioning
confidence: 99%
“…Recent research on the use of multiple external representations for learning provides some further support for this view (e.g., Kolloffel, Eysink, de Jong, & Wilhelm, 2009). …”
Section: Generativitymentioning
confidence: 96%